Outcomes of reconstructive urinary tract surgery after pelvic radiotherapy. (4th May 2019) - Toia, Bogdan; Seth, Jai; Ecclestone, Hazel; Pakzad, Mahreen; Hamid, Rizwan; Greenwell, Tamsin; Ockrim, Jeremy
Abstract: Background: Pelvic radiotherapy causes tissue atrophy and fibrosis, leading to urinary tract dysfunction. Tissue ischaemia poses a significant surgical challenge. This study examined the urological sequelae of radiotherapy, types of reconstructive urological surgery (RUS) required and functional outcomes. Methods: A retrospective review was performed of all radiotherapy patients who underwent RUS at a tertiary centre between 2007–2017. Details including time from radiotherapy, pre-operative assessments, type of surgery performed and functional outcome were analysed. Results: Fifty-four patients were identified. The primary malignancy was cervical (32), colorectal (9) and other urogenital/metastatic origins in the remaining cases. Mean time between radiation and RUS was 13 years. Sixty-nine reconstructive surgeries were performed. Twenty-two patients had fistulae, but only 27% were closed and 73% ended with urinary diversion. Eighteen had ureteric strictures, with 56% having associated bladder dysfunction. Twelve (67%) patients had RUS, of whom 83% required bowel interposition, and 33% primary diversion. Nine of 24 patients with contracted bladders were reconstructed and eight remain functionally continent. Renal function stabilised or improved in 87%. Nine patients (17%) had Clavien 3 or 4 complications. Conclusions: A variety of complex, major RUS were required. In 61%, urinary diversion was necessary, with radiotherapy fistulae being a particular challenge and closed in only a third. In total, 37% of patients were reconstructed achieving functional continence and restoration of upper-tract drainage with renal function preservation. This surgery was at a cost of a re-intervention rate of 28% and significant morbidity in 17%. RUS in the radiotherapy field should be performed in centres with experience.